Where are we in the world of proteomics and bioinformatics?. (October 2012) - Bencharit, Sompop; Border, Michael B
The 2nd International Conference on Proteomics & Bioinformatics (Proteomics 2012) Las Vegas, NV, USA, 2–4 July 2012 The 2nd International Conference on Proteomics & Bioinformatics (Proteomics 2012) was a follow-up from the successful 1st conference in Hyderabad, India, in June 2011. This conference was sponsored by the OMICS group. Talks on a variety of proteomic and bioinformatic sciences were presented ranging from computation methods, intracellular organelle proteomics, cellular proteomics, to clinical biofluid/tissue proteomics. This conference provided an excellent avenue for a productive multidisciplinary interaction. Several human diseases, for example, diabetes, malaria, glaucoma, bone disorders and others as well as plant pharmacoproteomics and drug development were included. This report summarizes some of the highlights and prospectives presented at this conference.